2022
DOI: 10.1177/08920206221126640
|View full text |Cite
|
Sign up to set email alerts
|

The gender blindness of the education 5.0 framework: An obstruction to promotion opportunities for female academics in Zimbabwe

Abstract: This study explores the implications for the Education 5.0 framework on promotion opportunities for female academics in Zimbabwean universities. The framework emphasises research, lecturing, community service, innovation and industrialisation as job performance areas for a university lecturer. The qualitative research adopted a multi-case study design and purposively sampled 24 female lecturers from two universities in Zimbabwe. Data were collected through in-depth interviews, focus group discussions and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Along these lines, ref. [26] also concludes that the lack of funding for research activities and training in scientific writing are two of the main obstacles identified by teachers in their expectations of the operational framework of Education 5.0, which mainly affects female academics.…”
Section: Toward Digital Transformation and Technological Innovation I...mentioning
confidence: 99%
“…Along these lines, ref. [26] also concludes that the lack of funding for research activities and training in scientific writing are two of the main obstacles identified by teachers in their expectations of the operational framework of Education 5.0, which mainly affects female academics.…”
Section: Toward Digital Transformation and Technological Innovation I...mentioning
confidence: 99%
“…In Mexico, Maheshwari et al (2023) studied factors influencing women academics, examining both enablers (family support, societal impact, professional growth aspirations and role models for younger women) and barriers (work-life balance, fear, inadequate institutional support and social stigma). In Zimbabwean universities, Muchabaiwa and Chauraya (2022) highlighted the lack of gender policies hindering women academics' progress. They suggested the necessity of implementing policies addressing issues such as insufficient funding for research, inadequate training in scientific writing, and the additional burden of domestic responsibilities.…”
Section: Underrepresentation Of Women Academics In Stemmentioning
confidence: 99%
“…Various things can be done in integrated services to realize good governance in the era of Society 5.0, namely Adaptive, Integrity, and High Performance. Muchabaiwa & Chauraya (2022) stated that building an innovation center can operationalize the educational framework in the era of Society 5.0. In integrated services, it is appropriate to carry out bureaucratic reform because it is one way to realize good governance.…”
Section: Introductionmentioning
confidence: 99%